PERBANDINGAN PERUBAHAN KECEMBUNGAN WAJAH ANTARA JARINGAN KERAS DAN LUNAK PADA PERAWATAN MALOKLUSI ANGLE KLAS II DIVISI 1 (Kajian Sefalogram Perawatan Teknik Begg dengan Pencabutan Empat Gigi Premolar Pertama) - , Herna Juliana Nainggolan ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of orthodontic treatment with fixed appliance is Begg technique. Itâs Specific to treating Angle Class II division 1malocclusion, can cause bite opening, mandibular rotation, rectraction of anterior teeth and lip retraction was to correct facial profile. The purpose of this study was to determine the ratio of a change value angle of convexity between hard and soft tissue at GAPog, NAPog and GÎAÎPogÎ, NÎAÎPogÎ in patient with angle class II division 1 malocclussion after treatment with Begg technique fixed appliance. The study was carried out using 20 pairs of lateral cephalograms of class II division 1 malocclusion before and after in year of 2002- 2012 which the inclusion criterias. The study was carried out in orthodontic clinic in Faculty of Dentistry, Gadjah Mada University, Yogyakarta using cross-sectional, with quasi-experimental research method. Differences of angle of convexity of hard and soft tissue change after treatment were analyzed with paired t-test. The results of study showed that there was angle of convexity between hard and soft tissue after treatment very signinificant (p=0.00). Hard tissue change at NAPog 4,05Â° will be followed by change soft tissue NÎAÎPogÎ 2,4Â°. As 3,1Â°change at GAPog will be followed by 2,0Â° soft tissue change. It have as a conclusion is hard tissue change was bigger than soft tissueP